1995
DOI: 10.1136/pgmj.71.835.317-a
|View full text |Cite
|
Sign up to set email alerts
|

Polyorchidism: causation and management

Abstract: points * septic arthritis in an adult often has a predisposing factor * group B streptococcal septic arthritis in a woman should raise the possibility of a genitourinary source Organisms isolated from septic joints in pregnancy include Pseudomonas aeruginosa, Staphylococcus aureus, Mycoplasma hominis and our case of group B streptococcus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…A left‐sided preponderance of polyorchidism with a ratio of 3:1 has been documented 12–15 . In the most common form, polyorchidism presents as two testes with a common epididymis and single vas deferens 4 but variants with separate epididymis and vas deferens exist. Seventy‐five per cent of the supernumerary testes are intrascrotal, 20% inguinal and 5% retroperitoneal at presentation 16,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A left‐sided preponderance of polyorchidism with a ratio of 3:1 has been documented 12–15 . In the most common form, polyorchidism presents as two testes with a common epididymis and single vas deferens 4 but variants with separate epididymis and vas deferens exist. Seventy‐five per cent of the supernumerary testes are intrascrotal, 20% inguinal and 5% retroperitoneal at presentation 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested removal of supernumerary testis because of the risk of malignancy 18 . However, it is difficult to estimate the true malignant potential of polyorchidism alone because of the frequent association with conditions reported to be present in a significant proportion of polyorchidism, all known to be risk factors for malignancy 3–5,12–15,18 . Previously removal of the supernumerary testicle was advocated 14 with exploration allowing fixation of the testes to prevent torsion.…”
Section: Discussionmentioning
confidence: 99%
“…In about 4-7% of supernumerary testes, a malignant degeneration or transformation occurs [6,7] , and in approximately 50-65% of supernumerary testes, there is a chance of active spermatogenesis [1] . Several embryological mechanisms have been proposed, including the degeneration of parts of the mesonephric components, the duplication or division of the genital ridge [2] or the accidental longitudinal or transverse division of the genital ridge, with or without the mesonephros, before the 8th week of gestation, either by a local accident or by the development of peritoneal bands [1] .…”
Section: Discussionmentioning
confidence: 99%
“…More recently, with advances in ultrasound and MRI technology, more conservative approaches have been advocated, as carried out in our case, in a normal, uncomplicated and orthotopic supernumerary testis [12] . Conversely, surgical exploration is mandatory, whenever the nature of the testicular mass remains unclear, with the added advantage of allowing the fixation of the testes to prevent torsion and the creation of a single testicular mass in certain cases, and biopsy to reveal the histological pattern [6] . Indications for a removal include malignant or dysplastic change on biopsy, and in those circumstances when the regular follow-up is unlikely to be reliable.…”
Section: Managementmentioning
confidence: 99%
“…Patients may present with pain or scrotal swelling. Most commonly abnormalities are maldescent (40%), hernia (30%), torsion (15%), hydrocele (9%) and malignancy (6%) [2].…”
mentioning
confidence: 99%